Hymenoscyphus pseudoalbidus, the causal agent of European ash dieback. (7th October 2013) - Gross, Andrin; Holdenrieder, Ottmar; Pautasso, Marco; Queloz, Valentin; Sieber, Thomas Niklaus
Summary: The ascomycete Hymenoscyphus pseudoalbidus (anamorph Chalara fraxinea ) causes a lethal disease known as ash dieback on Fraxinus excelsior and Fraxinus angustifolia in Europe. The pathogen was probably introduced from East Asia and the disease emerged in Poland in the early 1990s; the subsequent epidemic is spreading to the entire native distribution range of the host trees. This pathogen profile represents a comprehensive review of the state of research from the discovery of the pathogen and points out knowledge gaps and research needs. Taxonomy: Members of the genus Hymenoscyphus (Helotiales, Leotiomycetidae, Leotiomycetes, Ascomycota) are small discomycetes which form their ascomata on dead plant material. A phylogeny based on the internal transcribed spacers (ITSs) of the rDNA indicated the avirulent Hymenoscyphus albidus, a species native to Europe, as the closest relative of H. pseudoalbidus . Symptoms: Hymenoscyphus pseudoalbidus causes necrotic lesions on leaves, twigs and stems, eventually leading to wilting and dieback of girdled shoots. Bark lesions are characterized by a typical dark‐ to cinnamon‐brown discoloration. Life cycle: Hymenoscyphus pseudoalbidus is heterothallic and reproduces sexually on ash petioles in the litter once a year. Ascospores are wind dispersed and infect ash leaves during the summer. The asexual spores only serve as spermatia. Tools and techniques: The most important techniques for fungal handling, such as detection, isolation, culturing, storage, crossing and ascocarp production, are briefly described. Management: Once the disease is established, management is hardly possible. The occurrence of a small fraction of partially tolerant trees constitutes hope for resistance breeding in the future. Healthy‐looking trees should be preserved.